Parent Knowledge of Screening and Genetic Testing in Retinoblastoma - Wei Xiao; Xian Ji; Huijing Ye; Huiqi Zeng; Yang Gao; Rongxin Chen; Xiaoyun Chen; Yuxiang Mao; Huasheng Yang (Journal of Ophthalmology)
Purpose. To evaluate parent knowledge of screening and genetic testing for retinoblastoma and its potential correlation with demographics, clinical features, and socioeconomical factors. Methods. It was a cross-sectional study conducted at the ocular oncology unit of a tertiary ophthalmic center in Southern China. A face-to-face interview was administered to parents of retinoblastoma children during hospitalization. Parent knowledge was assessed using the sum score of a 7-item questionnaire. Demographics and socioeconomic status were collected from the interview, and clinical data were retrieved from the medical records. Results. A total of 126 parents of retinoblastoma children were included. Parents accurately answered 66.7% to 84.9% of each item in the questionnaire. Only 37 (29.4%) parents correctly answered all 7 questions. Parent knowledge was positively correlated with education, but it was not associated with patients’ laterality, sex, or household income. Physicians and the Internet were the major sources of parental health-related information. During the median follow-up of 492 days, 13 (61.9%) of 21 patients in the full-score group without genetic testing at baseline actually conducted testing during follow-up compared to 29 of 67 (43.3%) in the less-than-full-score group (P=0.136). Conclusion. Overall parent knowledge about retinoblastoma screening and genetic testing was moderate. Higher education was associated with greater parent knowledge. Future studies should validate our findings in other populations, especially in those with different cultural background and healthcare systems.